Influential factors of corporate involvement in community resilience governance from the perspective of symbiosis theory - Huang, Jing; Liu, Yi (Frontiers in Energy Research, 2024)
Urban resilience is a new paradigm for urban risk governance, whereas developing community resilience is the foundation for better resilient governance. Corporations serve as both the foundation and pivotal factor in ensuring the resilience of a community. Therefore, it is vital to encourage their active involvement in community resilience governance. This investigated the key influential factors of corporations in community resilience governance as well as the influence paths related to these factors. Firstly, multi-participant symbiotic relationships in the community resilience symbiosis system were analyzed. The hypothesis model of corporations' involvement in community resilience governance was proposed, combining the Theory of Planned Behavior and the Theory of Social Practice. Finally, the subjective and objective factors and influence paths were explored based on the structural equation model and the linear regression model by questionnaire investigation. The results show that: (1) Corporate involvement behavior is influenced by subjective factors such as behavioral attitude (ATT), subjective norm (SN), perceived behavioral control (PBC), and behavioral intention (BI), and also by objective community institutional factors including Field and Social capital. (2) The five influence paths to behavior (B) are as follows: SN→ATT→BI→B; PBC→ATT→BI→B; PBC→B; Field × BI → B; and Social capital × BI → B. (3) The involvement behavior is the result of a combination of rational and moral reasoning, with rationality preceding morality. Field capital and Social capital positively and negatively moderate the transformation of behavioral intention into behavior, respectively.